Віковий дефіцит андрогенів у чоловіків. Сучасні підходи до діагностики та лікування - Кирилюк, М. Л. (Clinical Endocrinology and Endocrine Surgery, 2013)
The lecture presents data on epidemiology, classification, etiology and pathogenesis, clinic, diagnostics and modern treatment of late-onset male androgen deficiency syndrome.